Alternative strategies to reduce liver abscess incidence and severity in feedlot cattle. - Müller, Hans Christian (Kansas State University, 2017)
Since the 1960’s liver abscess incidence and severity have been identified as a problem associated with feeding high concentrate finishing rations to feedlot cattle. Liver abscesses lead to decreased feedlot performance and decreased carcass value. Tylosin phosphate is a macrolide antibiotic commonly used by feedlots throughout the United States and has been shown to successfully control liver abscesses. In 2013, the FDA issued Guidance for Industry #213, which encourages reduced usage of medically important classes of antibiotics, such as macrolides, in animal feed. This will be achieved by implementing veterinary oversight of these drugs via Veterinary Feed Directives (VFD). Thus, it is of importance to find alternative strategies to reduce usage of tylosin in finishing rations to control liver abscesses. One strategy that has been suggested is increasing dietary roughage concentration. However, this isn’t a viable option as increasing dietary roughage concentration not only leads to a decline in feedlot performance, hot carcass weight, and dressing percentage, but also has an environmental impact. Available research has also indicated that increasing dietary roughage has no impact on liver abscess incidence or severity. Our research objective was therefore to identify alternative strategies to reduce liver abscess incidence. Our first trial evaluated the impact of antioxidants on liver abscess incidence and severity. Treatments consisted of a control treatment (basal diet containing 200 IU/d α-tocopherol acetate), and an antioxidant treatment (basal diet containing 2000 IU/d α-tocopherol acetate and 500 mg/d crystalline ascorbate). Treatments were randomly assigned to 390 crossbred heifers. No differences in feedlot performance were detected; however, there was a tendency for improved feed intake (P = 0.075) and feed efficiency (P = 0.066) for heifers that received the antioxidant treatment. An increased number of yield grade 3 carcasses (P = 0.03) and fewer yield grade 1 carcasses (P < 0.01) was observed in the antioxidant treatment group. No differences were detected between treatments for other carcass characteristics or liver abscess incidence and severity. Another trial evaluated intermittent tylosin feeding and its impact on liver abscess incidence and antimicrobial resistant Enterococcus spp. when compared to continuous tylosin feeding. One of 3 treatments were randomly assigned to 312 crossbred steers: negative control (no tylosin fed throughout the feeding period); positive control (tylosin fed throughout the feeding period); or intermittent treatment (tylosin fed intermittently throughout the feeding period: 1week on, 2 weeks off). Fecal samples were collected on day 0, 20, and 118 to characterize antimicrobial resistant Enterococcus spp. By design, the intermittent treatment consumed 60% less tylosin than the positive control group. No differences were detected between treatments for feedlot performance. Liver abscess incidence was greatest for the negative control, and least for the positive control and intermittent treatments, with no difference being detected between the latter two treatments (P = 0.716). Antimicrobial resistance was unaffected by treatment, but was affected by sampling time. We concluded that supplementing antioxidants is not a viable option to reduce liver abscess incidence and severity, and that tylosin usage can be decreased without adversely affecting performance or liver abscess incidence.
Keywords: Liver abscess; Tylosin; Antioxidant; Intermittent; Feedlot